Islam Dan Agama Lokal Dalam Arus Perubahan Sosial - Tendi, Tendi (AL-TAHRIR, 2016)
Abstract: Agama Djawa Soenda (ADS)( Djawa Soenda religion) is one of the local beliefs that bases in Cigugur, Kuningan, West Java. Among three eras of leaderships that existed there, the leadership of Tedjabuana prince was the most unique one because ADS developed in three different periods: the Dutch colonial rule; the Japanese occupation; and the Indonesian independence. Social change in the period of Tedjabuana had made ADStrapped several times in the vortex of conflict with a number of Muslims. The conflict could end when the new ruler, who was close to Islam, pressed the ADS follower until their group dissolved. The method used in this study was historical method with a qualitative descriptive analysis through the sociological-anthropological perspective. In this study, data collection was done by collecting various kinds of information from some literatures, social and cultural data that were found in the research field through observation and interviews process to support the validity of the data that was successfully obtained. The results showed that the big challenges faced by ADS from 1939 to 1964 was the result of the fast social change that had influenced almost all aspects of community life, including the religious aspect. The social changes led ADS to a conflict that had made it development stagnant and even paralyzed.Â Ø§Ù„Ù…Ù„Ø®Øµ: ÙƒØ§Ù† Ø§Ø¹ØªÙ‚Ø§Ø¯ Ø¬Ø§ÙˆØ© ÙˆØ³ÙˆÙ†Ø¯Ø§ (Agama Djawa Soenda, ADS) Ù…Ù† Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯Ø§Øª Ø§Ù„Ù…ØÙ„ÙŠØ© Ø§Ù„Ù…ØªÙ…Ø±ÙƒØ²Ø© ÙÙŠ Ø¬ÙŠØºÙˆØºÙˆØ± ÙƒÙˆÙ†ÙŠÙ†Ø¬Ø§Ù† Ø¬Ø§ÙˆØ© Ø§Ù„ØºØ±Ø¨ÙŠØ©. ÙˆÙ…Ù† ÙØªØ±Ø§Øª Ø«Ù„Ø§Ø« Ø±Ø¦Ø§Ø³Ø§Øª ÙƒØ§Ù†Øª Ø±Ø¦Ø§Ø³Ø©Â  Ø§Ù„Ù…Ù„Ùƒ ØªÙŠØ¬Ø§Ø¨ÙˆØ§Ù†Ø§ ÙƒØ§Ù†Øª Ø±Ø¦Ø§Ø³Ø© Ø®Ø§ØµØ© Ù…ØªÙ…ÙŠÙ‘Ø²Ø© Ù„Ø£Ù† ÙÙŠÙ‡Ø§ ØªØ·ÙˆÙ‘Ø± Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯ ÙÙŠ Ø«Ù„Ø§Ø« ÙØªØ±Ø§Øª Ù…Ø®ØªÙ„ÙØ© Ù‡ÙŠ ÙØªØ±Ø© Ø§Ù„Ø§Ø³ØªØ¹Ù…Ø§Ø± Ø§Ù„Ù‡ÙˆÙ„Ù†Ø¯Ù‰ØŒ ÙˆØ§Ù„Ø§Ø³ØªØ¹Ù…Ø§Ø± Ø§Ù„Ø¥Ù„ÙŠØ§Ø¨Ø§Ù†ÙŠ ÙˆÙØªØ±Ø© "Ø§Ù„Ø§Ø³ØªÙ‚Ù„Ø§Ù„". ÙˆÙˆØ¬ÙˆØ¯ Ø§Ù„ØªØºÙŠÙ‘Ø±Ø§Øª ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ ÙÙŠ Ø¹Ù‡Ø¯ Ø§Ù„Ù…Ù„Ùƒ ØªÙŠØ¬Ø§Ø¨ÙˆØ§Ù†Ø§ Ø¬Ø¹Ù„ ( ADS)Â  ÙŠÙ‚Ø¹ ÙÙŠ Ø¹Ø¯Ù‘Ø© Ù†Ø²Ø§Ø¹Ø§Øª Ø¨ÙŠÙ†Ù‡ ÙˆØ¨ÙŠÙ† Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ†. ØªÙ†ØªÙ†Ù‡ÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ù†Ø²Ø§Ø¹Ø§Øª Ø¹Ù†Ø¯Ù…Ø§ Ø§Ù‚ØªØ±Ø¨ Ø§Ù„Ø±Ø¦ÙŠØ³ ØÙŠÙ† Ø°Ø§Ùƒ Ù…Ù† Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† ÙˆØ¶ØºØ· Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯ÙŠÙ† Ù„ (ADS) ØØªÙ‰ Ù‚Ø¶ÙŠ Ø¹Ù„Ù‰ Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯. ÙˆØ§Ù„Ø·Ø±ÙŠÙ‚Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø§Ù„Ø¹Ù„Ù…ÙŠ Ù‡ÙŠ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠ Ø¨Ø§Ù„Ù…Ø¯Ø®Ù„ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„ÙƒÙŠÙÙŠÂ  Ø¨Ù…Ù†Ø¸Ø§Ø± Ø¥Ø¬ØªÙ…Ø§Ø¹ÙŠ Ø£Ù†ØªØ±ÙˆØ¨ÙˆÙ„ÙˆØ¬ÙŠÙ‘. ÙˆÙ„Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¬Ù…Ø¹ Ø§Ù„Ø¨Ø§ØØ« Ø´ØªÙ‘Ù‰ Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ù…Ù† Ø§Ù„ÙˆØ«Ø§Ø¦Ù‚ Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø© ÙˆÙ…Ù† Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© ÙˆØ§Ù„Ø«Ù‚Ø§ÙÙŠØ© Ø§Ù„ØªÙŠ ÙˆØ¬Ø¯Ù‡Ø§ ÙÙŠ Ù…ÙŠØ¯Ø§Ù† Ø§Ù„Ø¨ØØ« Ø¹Ù† Ø·Ø±ÙŠÙ‚ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© Ø§Ù„Ø´Ø®ØµÙŠØ© ÙƒØªØ£ÙƒÙŠØ¯Ø§Øª Ù„ØµØØ© Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª. Ø¯Ù„Ù‘Øª Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« Ø¹Ù„Ù‰ Ø£Ù† Ø§Ù„Ù…Ø´Ø§ÙƒÙ„ Ø§Ù„ØªÙ‰ ÙŠÙˆØ§Ø¬Ù‡Ù‡Ø§ Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯ Ù…Ù† Ø§Ù„Ø³Ù†Ø© 1939 Ù… â€“ 1964Ù… Ù‡ÙŠ Ù†ØªÙŠØ¬Ø© Ù„ÙˆÙ‚ÙˆØ¹ Ø§Ù„ØªØºÙŠÙ‘Ø±Ø§Øª Ø§Ù„Ø³Ø±ÙŠØ¹Ø© ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…Ø¤Ø«Ø±Ø© ÙÙŠ Ø¬Ù…ÙŠØ¹ Ù†ÙˆØ§ØÙŠ ØÙŠØ§ØªÙ‡ ÙˆÙ…Ù†Ù‡Ø§ Ø§Ù„Ø¬Ø§Ù†Ø¨ Ø§Ù„Ø¯ÙŠÙ†ÙŠ. Ø£Ø¯Ù‘Øª Ù‡Ø°Ù‡ Ø§Ù„ØªØºÙŠÙ‘Ø±Ø§Øª Ø¥Ù„Ù‰ ÙˆÙ‚ÙˆØ¹ Ø§Ù„Ù…Ø´Ø§ÙƒÙ„ Ø§Ù„ØªÙŠ ØªØ³Ø¨Ø¨ Ø¥Ù„Ù‰ ØªÙˆÙ‚Ù‘Ù (ADS) ÙˆÙ…ÙˆØªÙ‡.Â Abstrak: Agama Djawa Soenda (ADS) merupakan salah satu kepercayaan lokal yang berpusat di Cigugur, Kuningan, Jawa Barat. Di antara tiga masa kepemimpinan yang ada, masa kepemimpinan Pangeran Tedjabuana merupakan masa yang paling unik karena ADS berkembang dalam tiga masa yang berbeda, yaitu masa pemerintahan kolonial Belanda, masa pendudukan Jepang, dan masa kemerdekaan. Perubahan sosial pada masa Tedjabuana membuat ADS terjebak beberapa kali dalam pusaran konflik dengan sejumlah kalangan muslim, Konflik itu baru dapat berakhir ketika penguasa, yang saat itu dekat dengan kaum Islam, menekan para penghayat ADS sehingga kemudian dibubarkan. Metode penelitian yang digunakan adalah metode sejarah dengan pendekatan deskripsi kualitatif melalui cara pandang sosiologis-antropologis. Dalam studi ini, pengumpulan data dilakukan dengan cara mengumpulkan pelbagai macam informasi yang ada dari pembacaan dokumen-dokumen sebagai sumber-sumber tertulis serta dari data-data sosial atau kultural yang ditemukan di lapangan melalui proses observasi (pengamatan) dan interview (wawancara) guna mendukung keabsahan data yang berhasil didapatkan. Hasil penelitian menunjukkan bahwa tantangan berat yang dihadapi oleh ADS dari tahun 1939 hingga 1964 merupakan buah dari perubahan sosial cepat yang telah memengaruhi hampir keseluruhan segi kehidupan masyarakat, termasuk di antaranya adalah aspek keagamaan. Perubahan sosial itu melahirkan konflik yang membuat perkembangan ADS menjadi stagnan dan bahkan lumpuh sama sekali.